Fibrinolysis in Trauma: “Myth,” “Reality,” or “Something in Between” - Walsh, Mark; Shreve, Jacob; Thomas, Scott; Moore, Ernest; Moore, Hunter; Hake, Daniel; Pohlman, Tim; Davis, Patrick; Ploplis, Victoria; Piscoya, Andres; Wegner, Julie; Bryant, John; Crepinsek, Anton; Lantry, James; Sheppard, Forest; Castellino, Francis (Seminars in Thrombosis and Hemostasis, 2017)
The emphasis on fibrinolysis as an important contributor to trauma-induced coagulopathy (TIC) has led to a debate regarding the relative clinical significance of fibrinolysis in the setting of trauma. The debate has centered on two camps. The one camp defines fibrinolysis in trauma by standard coagulation tests as well as fibrin split products, D-dimers, and plasmin/antiplasmin levels. This camp favors a more liberal use of tranexamic acid and attributes more significance to hyperfibrinolysis in TIC. The other camp favors a definition of fibrinolysis based on the viscoelastic tests (VET), rotational thromboelastometry (ROTEM), and thromboelastography (TEG). These whole blood assays define hyperfibrinolysis at a higher threshold than plasma-based tests. Therefore, this VET camp reserves antifibrinolytic treatment for patients who demonstrate severe coagulopathy associated with hyperfibrinolysis. This bimodal attribution of the clinical relevance of fibrinolysis in trauma suggests that there may be an underlying “Myth” of the concept of TIC that was historically defined by plasma-based tests and a future “Reality” of the concept of TIC that is grounded on an understanding of TIC based on a VET-defined “fibrinolytic spectrum” of TIC. This narrative review explores this “Myth” and “Reality” of fibrinolysis in TIC and proposes a direction that will allow a “Future” interpretation of TIC that incorporates both the past “Myth” and present “Reality” of fibrinolysis TIC.
Keywords: fibrinolysis; trauma-induced coagulopathy; tranexamic acid; thromboelastography; rotational thromboelastometry; fibrinolytic spectrum; fibrinolytic shutdown; tissue injury phenotype; hyperfibrinolysis; hemorrhagic phenotype; activated protein C